Correlation of Cryptococcal Antigen Assay with C-reactive Protein as Serum and Urine Biomarker in Cryptococcal Meningitis: Experience in a Tertiary Hospital - Bineeta Kashyap; Rajat Jhamb; Shukla Das; Neha Berry; Iqbal R Kaur (Journal of Clinical Research In HIV AIDS And Prevention, 2013)
Aims and Objectives: The incidence of cryptococcal meningitis caused by Cryptococcus neoformans has risen markedly over the past 20 years as a result of theHIV epidemic and increasing use of immunosuppressive therapies. The objectives of this study were to isolate and identify Cryptococcus neoformans from clinically suspected cases of fungal meningitis by conventional techniques and evaluate the role of C-reactive protein (CRP) as a serum or urine biomarker for the diagnosis and monitoring of patients with cryptococcal meningitis. Materials and Methods: Direct microscopic examination of the CSF samples from clinically suspected cases of fungal meningitis was done by India Ink staining for the capsule demonstration and isolation of the Cryptococcus neoformans was done by inoculation of the sample on Sabourauds dextrose agar. Latex agglutination test for the presence of cryptococcal antigen was done on sera, CSF and urine samples. C Reactive Protein levels were estimated in sera and urine. Result: Cryptococcal meningitis was diagnosed in 12 cases by culture and/or India Ink staining and/or latex agglutination assay for antigen detection in CSF. Only 8 (66.67%) and 1 (8.33 %) out of 12 samples were positive for cryptococcal antigen in sera and urine respectively. Whereas all the 12 patients were positive in the sera for CRP above the detection threshold limit, only 1 (8.33 %) patient had raised CRP in urine. CRP was raised two weeks after initiation of antifungal therapy in 3 of the above 12 sera and all these 3 cases turned out to be recurrent cases of cryptococcal meningitis. Conclusion Given the high incidence, morbidity and mortality associated with cryptococcal meningitis, it would be ideal if a screening test could be used to exclude this diagnosis based on the presence of biomarkers in serum or urine which would mean less discomfort for the patient in addition to decreased laboratory examination costs.
Keywords: Cryptococcal Meningitis